Tribological characteristics of 'steel-ceramics-irradiated-by-helium-ions' pair - Butenko, V.I.; Dubniuk, S.N.; Dyachenko, A.F.; Pavlii, K.V.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2021)
Facility for the tribological characteristics studying of a metal – ceramics pair and parameters of ceramic samples irradiation on the helium ions linear accelerator with energies 0.12 and 4 MeV are resulted. Profiles of damageability and occurrence of target atoms along of helium ions range are calculated for the irradiated TiO₂ and Al₂O₃. Sputtering ratios and dependence of the sputtered atoms quantity on samples thickness are received. Calculations on density change of the irradiated samples are made. Experimental results of a sliding friction factor measurement depending on cycle’s quantity, temperature and irradiation doses are presented. On the basis of microscopic researches and calculation data conclusions are drawn about irradiation influence on interacting pair’s tribological characteristics.